2013
DOI: 10.2478/pjvs-2013-0075
|View full text |Cite
|
Sign up to set email alerts
|

Changes in blood acid-base balance parameters and coagulation profile during diarrhea in calves

Abstract: The purpose of this study was to investigate possible alterations in acid-base balance parameters and the coagulation profile in neonatal diarrheic calves. Twenty neonatal diarrheic and 20 clinically healthy neonatal calves aged between 1 week to 10 days were used. All blood samples were taken on the third day from the onset of diarrhea symptom. Venous blood samples were collected from each animal to determine platelet numbers, pH, pCO 2 , pO 2 , HCO 3-, BE, O 2 SAT, ctCO 2 and electrolytes (K + , Na + and Cl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
19
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 26 publications
4
19
1
2
Order By: Relevance
“…High levels in D-dimer in sick animals most probably resulted from the activation of intravascular fibrinolysis. Other coagulation parameters obtained from healthy cattle such as fibrinogen (216.50 ± 10.55 mg/dl); TT (24.80 ± 1.77 sec); PT (27.53 ± 1.55 sec) and aPTT (27.43 ± 3.35 g/dL) were concomitant with the results of earlier studies (Gentry et al 1979, Sobiech et al 2013, Karakurum et al 2009). Although different analysers have been used in the above studies, these results were very close to each other and reinforced the accuracy of the data obtained from the present study.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…High levels in D-dimer in sick animals most probably resulted from the activation of intravascular fibrinolysis. Other coagulation parameters obtained from healthy cattle such as fibrinogen (216.50 ± 10.55 mg/dl); TT (24.80 ± 1.77 sec); PT (27.53 ± 1.55 sec) and aPTT (27.43 ± 3.35 g/dL) were concomitant with the results of earlier studies (Gentry et al 1979, Sobiech et al 2013, Karakurum et al 2009). Although different analysers have been used in the above studies, these results were very close to each other and reinforced the accuracy of the data obtained from the present study.…”
Section: Discussionsupporting
confidence: 74%
“…Radwyńska (2010) found that D-dimer concentrations in BVD-MD infected cows were higher (1180.47 ± 62.81 μg/L) than those of non-infected cows (159.27 ± 26.81 μg/L). Blood concentrations of D-dimer and some coagulation parameters have been described as accurate indicators of cattle with left displacement of abomasum (688.07 ± 168.26 μg/l) and diarrhoeic calves (587.25 μg/l) (Sobiech et al 2013, Radwinska 2010. Wittek et al (2010) also stated that peritoneal fluid D-dimer was most accurate in diagnosis of cattle with peritonitis compared to the other some parameters.…”
Section: Discussionmentioning
confidence: 99%
“…This could be indicative of compensation of metabolic acidosis as well as an inflammation of the GI tract and loss of buffer through feces. Hyperkalemia is a common electrolyte disturbance in diarrheic calves [57][58][59] and blood pH, base excess, and HCO 3 − were lower, whereas serum K and Na were elevated in diarrheic calves compared to clinical healthy calves [60]. Trefz et al [61] reported that serum potassium concentrations >5.8 mmol/L were more closely associated with dehydration and diarrhea than with decreases in base excess or venous blood pH.…”
Section: Discussionmentioning
confidence: 99%
“…The diarrheic calf becomes dehydrated and suffers from electrolyte loss and acidosis. In addition to its effects on gastrointestinal system, it also effects other systems or organ functions such as lungs, kidneys, and liver [ 25 ].…”
Section: Discussionmentioning
confidence: 99%